IMPLEMENTASI SOLAR PUMP UNTUK IRIGASI LAHAN PERTANIAN PADA KELOMPOK TANI " EKO MULYO" PRAMBANAN - Budiati, Haeni; Setyowati, Emerita; Jacobus, Liefson (Jurnal Abdimas Bina Bangsa, 2024)
The "Eko Mulyo" Madurejo Prambanan Sleman farming group has 12 hectares of dry rice fields. Farmers who are economically well off usually build drilled wells and use generators for irrigation during the dry season, while less well off farmers only use existing irrigation. Water quotas sometimes do not reach the land. As a result, rice production decreases during the long dry season. To overcome this problem, a solar water pump was installed. Solar water pump components include a solar module to convert solar radiation into electrical energy, a pump controller to control the pump and a submersible water pump to pump groundwater to the surface. Solar pump systems can be monitored in real time using a pump scanner installed on a smartphone. The results of the monitoring system were a water discharge of 1.5-1.6 m3/hour with the total water pumped over 8 days was 91.8 m3 and the total energy produced was 0.85 kWh. The advantages of using solar pump were more economical and efficient in pumping water because it uses renewable energy